2019
DOI: 10.3390/w11040864
|View full text |Cite
|
Sign up to set email alerts
|

Suitable Site Selection for Rainwater Harvesting and Storage Case Study Using Dohuk Governorate

Abstract: The Middle East is an inherently dry zone. It has experienced severe drought for the last seven years, and climate change has made the situation worse. The Dohuk governorate has been suffering from an appalling water crisis. One possible way of relieving this water crisis is by properly harvesting the rainwater. Rainwater harvesting is a widely used method of storing rainwater in the countries presenting with drought characteristics. Several pieces of research have derived and developed different criteria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…Typical contaminants occurring in rainwater, and the factors influencing rainwater quality are discussed in detail in earlier papers [46,47]. In summary, depending on roof materials, land use, climatic factors and storage conditions, rainwater may contain contaminants such as trace metals, pathogenic organisms, and physical objects (e.g., leaves, bird and animal droppings) [31,32,[46][47][48]. Thus preliminary analysis and subsequent treatment using low-cost methods may need to be considered on a case-by-case basis.…”
Section: Overview Of the Kilimanjaro Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical contaminants occurring in rainwater, and the factors influencing rainwater quality are discussed in detail in earlier papers [46,47]. In summary, depending on roof materials, land use, climatic factors and storage conditions, rainwater may contain contaminants such as trace metals, pathogenic organisms, and physical objects (e.g., leaves, bird and animal droppings) [31,32,[46][47][48]. Thus preliminary analysis and subsequent treatment using low-cost methods may need to be considered on a case-by-case basis.…”
Section: Overview Of the Kilimanjaro Conceptmentioning
confidence: 99%
“…Thus preliminary analysis and subsequent treatment using low-cost methods may need to be considered on a case-by-case basis. Recently, some studies have investigated the following: (i) surface treatments for enhancing rainwater harvesting [30], (ii) site selection for rainwater harvesting and subsequent storage systems [32], and (iii) the effects of climate change and variability on urban rainwater harvesting systems [33]. These recent studies provide critical information for the implementation of the Kilimanjaro Concept.…”
Section: Overview Of the Kilimanjaro Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Duhok's Environment Protection Department, Duhok City has been more toxic than ever due to the 2000 registered power generators [55]. In addition, Eklund and Seaquist showed that there is a significant decline in rainy season in the city due to the changes in climatic conditions [56]. During the hydrological years 2006-2009, the accumulated rainfall dropped to almost 50% below the 2000-2010 total average of 368 mm [57].…”
Section: The Case Study Area and Its Sustainability Objectivesmentioning
confidence: 99%
“…Limited studies conducted on the influence of rainwater harvesting techniques on runoff and infiltration pattern suggested that itis a widely used groundwater recharge method by storing rainwater in the countries suffered with drought characteristics [16][17].…”
Section: Introductionmentioning
confidence: 99%